Correlation Between Intensity Of Students 'Participation In Religion Extraculicular Activities With Student Religion Behavior In Palembang Muhammadiyah 1 High School - Karliana Indrawari (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
Abstract: The study aims to determine the intensity of student participation in religious extracurricular activities, to determine the religious behavior of students, and to determine the correlation between the intensity of student participation in religious extracurricular activities and religious behavior. The type of research used is field research. The research samples was 75 students. The research instruments were observation, questionnaires, documentation, and interviews. Data analysis techniques by analyzing observation data, documentation, questionnaires and interviews, and interpretations. The results of this research are the level of intensity of the Senior High School of Muhammadiyah 1 Palembang high school students in attending religious extracurricular activities is classified as high and medium. The religious behavior of Senior High School of Muhammadiyah 1 Palembang students is classified as high and medium.